Pola Asuh Orang Tua dalam Mengembangkan Prestasi Belajar Siswa Kelas III SD Muhammadiyah 24 Gajahan Surakarta Tahun Pelajaran 2016/2017 - Aprilia, Vita Avie; , Drs. Rubino Rubiyanto, M.Pd (2017)
This study aims to describe a wide variety of parenting and parental effort in developing academic achievement's third grade students of SD Muhammadiyah 24 Gajahan Surakarta in the academic year 2016/2017. This study uses a qualitative approach with descriptive qualitative research design. The data collection technique used are questionare observation, interviews, and documentation. The data analysis includs data reduction, data presentation, and conclusion. And the data validity by triangulation of sources and techniques. Based on the results of this study, it is concluded that parents' parenting is divided into three kinds, namely authoritative parenting (unreliable), authoritarian and permissive. Parents will be developing their children's academic achievement in accordance with their respective parenting. Therefore, if the parental efforts done by parents in developing their children's learning achievement are done with suitable parenting, then their children's personality will always be affected in a good way.